Compressive Strength, Chloride Binding Capacity and Chloride Diffusion Coefficient of Concrete Containing Ground Bottom Ash and Limestone Powder - Warinlai, Banyut; Krammart, Pitisan (RMUTP Research Journal Sciences and Technology, 2022)
This research was aimed to study the compressive strength, chloride binding capacity and chloride diffusion coefficient of concrete replaced by ground bottom ash (GBA), and limestone powder in ordinary Portland cement (OPC). The water to binder ratios were 0.55. The results showed that the compressive strength of concrete with GBA was lesser than that of OPC concrete at 28 days. Also, the compressive strength of concrete with limestone powder was close to that of OPC concrete and compressive strength could develop of concrete with GBA 20% and 30% higher than that of OPC concrete at 56 days. Moreover, the total chloride of the concrete containing GBA and limestone powder was less than that of OPC concrete. The chloride penetration of the concrete containing GBA and limestone powder was less than that of OPC concrete. The chloride binding capacity of the concrete made with ground bottom ash and limestone powder were higher than that of OPC concrete. Finally, the chloride diffusion coefficient of the concrete containing GBA and limestone powder was less than that of OPC concrete.